Menjaga Kualitas Obat Lewat Edukasi Beyond Use Date (BUD) di Puskesmas Sumbang II Banyumas - prabandari, rani; Ammanu Kurniadi; Andrea Arum Sekar; Anisa Rakhma Diantri; Armelia Allya Sandika; Bellina Faradhita Luxfi (Jurnal Dimas, 2025)
Introduction: Because drug abuse and other issues may arise from the increased use of pharmaceuticals without proper understanding, determining the Beyond Use Date (BUD) is of the utmost importance. Since women may serve as "home pharmacists" and encourage self-sufficiency in health management, it is crucial to educate them about BUD. The goal of this pharmacist-led community service project is to educate housewives about BUD so that they may better manage their medications at home. Approach: Conversation and socializing were the tools used. By comparing the pre- and post-test scores, we were able to determine how helpful the therapy was. We distributed educational materials via BUD-related pamphlets. Higher post-test results compared to the pre-test showed that education on BUD increased knowledge. Conclusion: The PKK (Family Welfare Empowerment) members' understanding of BUD was enhanced by this Pharmacist Community Service activity's use of socializing and discussion to impart information.. Keywords—BUD, Drugs, Education